High species diversity and turnover in granite inselberg floras highlight the need for a conservation strategy protecting many outcrops. Issue 13 (13th June 2019) - Yates, Colin J.; Robinson, Todd; Wardell‐Johnson, Grant W.; Keppel, Gunnar; Hopper, Stephen D.; Schut, Antonius G. T.; Byrne, Margaret
Abstract: Determining patterns of plant diversity on granite inselbergs is an important task for conservation biogeography due to mounting threats. However, beyond the tropics there are relatively few quantitative studies of floristic diversity, or consideration of these patterns and their environmental, biogeographic, and historical correlates for conservation. We sought to contribute broader understanding of global patterns of species diversity on granite inselbergs and inform biodiversity conservation in the globally significant Southwest Australian Floristic Region (SWAFR). We surveyed floristics from 16 inselbergs (478 plots) across the climate gradient of the SWAFR stratified into three major habitats on each outcrop. We recorded 1, 060 species from 92 families. At the plot level, local soil and topographic variables affecting aridity were correlated with species richness in herbaceous (HO) and woody vegetation (WO) of soil‐filled depressions, but not in woody vegetation on deeper soils at the base of outcrops (WOB). At the outcrop level, bioclimatic variables affecting aridity were correlated with species richness in two habitats (WO and WOB) but, contrary to predictions from island biogeography, were not correlated with inselberg area and isolation in any of the three habitats. Species turnover in each of the three habitats was also influenced by aridity, being correlated with bioclimatic variables and with interplot geographic distance, and for HO and WO habitats with local site variables. At the outcrop level, species replacement was the dominant component of species turnover in each of the three habitats, consistent with expectations for long‐term stable landscapes. Our results therefore highlight high species diversity and turnover associated with granite outcrop flora. Hence, effective conservation strategies will need to focus on protecting multiple inselbergs across the entire climate gradient of the region. Abstract : Determining patterns of plant diversity on granite inselbergs is an important task for conservation biogeography due to mounting threats. We found species richness and composition in three inselberg habitats were correlated with local and regional environmental variables affecting aridity but not with island biogeographic variables. We found high species turnover among outcrops with species replacement and not nestedness being the dominant component. As a consequence strategies which focus on protecting multiple inselbergs rather than the largest or most species rich will best serve conservation of plant diversity.